Management and treatment of ankle sprain according to clinical practice guidelines: A PRISMA systematic review - Ruiz-Sánchez, Francisco Javier; Ruiz-Muñoz, María; Martín-Martín, Jaime; Coheña-Jiménez, Manuel; Pérez-Belloso, Ana J.; Romero-Galisteo, Rita Pilar; González-Sánchez, Manuel (Wolters Kluwer, 2022)
Background: The lateral sprain of the ankle is a very frequent injury in the population in general, appearing in the emergency services frequently. The general objective was to review the current clinical practice guidelines (CPGs) on management and treatment of ankle sprains, assess their quality, analyze the levels of evidence and summarize the grades of recommendation. Methods: A systematic search of the literature in relevant databases with the search terms “ankle,” “sprain,” “practice guideline,” and “guideline” was carried out. There were included those guidelines that had the system of grades of recommendation and level of evidence concerning to management and treatment of ankle sprain. The quality of the guides was assessed using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) tool. Results: Seven clinical practice guides were included in this review. The AGREE II scores ranged from 42% to 100%, with only six CPGs explicitly declaring the use of a systematic methodology. Seventeen recommendations were extracted and summarized. Discussion: Six of the recommendations analyzed present enough evidence to be applied in clinical practice and are highly recommended for ankle sprain management: Ottawa rules, manual therapy, cryotherapy, functional supports, early ambulation, short term NSAIDs and rehabilitation.
Keywords: Tobillos - Lesiones y heridas; Ankle; Guideline; Practice guideline; Review; Sprain